Rainwater major and trace element contents in Southeastern Brazil: an assessment of a sugar cane region in dry and wet period - Oliveira, Patrícia L.; Figueiredo, Bernardino Ribeiro de; Cardoso, Arnaldo Alves [UNESP] (Sociedade Brasileira de Química, 2012)
The purpose of this study was to assess the composition of the rainwater in Araraquara City, Brazil, a region strongly influenced by pre-harvest burning of sugar cane crops. Chemical and mineralogical variables were measured in rainwater collected during the harvest, dry period of 2009 and the non-harvest, wet period of 2010. Ca2+ and NH4+ were responsible for 55% of cations and NO3- for 45% of anions in rainwater. Al and Fe along with K were the most abundant among trace elements in both soluble and insoluble fractions. High volume weighted mean concentration (VWM) for most of the analyzed species were observed in the harvest, dry period, mainly due to agricultural activities and meteorological conditions. The chemistry of the Araraquara rainwater and principal component analysis (PCA) quantification clearly indicate the concurrence of a diversity of sources from natural to anthropogenic especially related to agricultural activities.

O objetivo deste estudo foi investigar a composição das águas de chuva da cidade de Araraquara, Brasil, uma região influenciada pela queima da palha da cana-de-açúcar. Variáveis químicas e mineralógicas foram analisadas em águas de chuva coletadas durante o período de safra, período seco de 2009 e entressafra, período úmido de 2010. Ca2+ e NH4+ foram responsáveis por 55% dos cátions e NO3- por 45% dos ânions presentes nas águas de chuva. Al, Fe e K foram os elementos traço mais abundantes nas frações solúvel e insolúvel. Elevada concentração média ponderada pelo volume (MPV) foi observada para a maioria das espécies analisadas em amostras do período de safra, principalmente devido às atividades agrícolas e condições meteorológicas. A química das águas de chuva de Araraquara e a análise de componentes principais (ACP) indicaram que fontes naturais e antrópicas, principalmente as relacionadas às atividades agrícolas, são responsáveis pelas emissões para a atmosfera.
Keywords: rainwater; trace elements; sugar cane crops; biomass burning; Brazil